International relations - Lawson, Stephanie (Short introductions, 2012)
International Relations emerged as a distinct academic discipline in the early twentieth century as scholars and practitioners sought to address the causes of war and conditions for peace in a systematic and sustained way. Its philosophic foundations, however, draw on centuries of thinking about human nature, political authority and obligation, justice and injustice, and their implications for relations within and between political communities. Since then, IR has become one of the most important and dynamic fields of academic study in the contemporary period. In this second edition, Stephanie Lawson retains a broad historical and contextual approach in introducing readers to the central themes and theoretical perspectives while also addressing key concerns in the contemporary period. These include the emergence of states and empires, theories ranging from classical realism and liberalism to postcolonial and 'green' theory, twentieth century international history, security and insecurity, global governance and world order, international political economy, globalization and the prospects for a 'postinternational' world. Written in an accessible narrative style, this book will appeal to students at undergraduate level and beyond, including those undertaking postgraduate coursework study in IR with little or no previous academic training in the field